Không tính giá trị cụ thể hãy so sánh hai biểu thức: (1+2+3+4) ² và 1³+2³+3³+4³ 21/09/2021 Bởi Alaia Không tính giá trị cụ thể hãy so sánh hai biểu thức: (1+2+3+4) ² và 1³+2³+3³+4³
Ta thấy : `(1+2)^2=1^3+2^3` `(1+2+3)^2=1^3+2^3+3^3` `⇒(1+2+3+4)^2=1^3+2^3+3^3+4^3` Từ đó, ta rút ra công thức : `[a+(a+1)+(a+2)+…+(a+n)]^2=a^3+(a+1)^3+(a+2)^3+…+(a+n)^3` Bình luận
Đáp án:
Giải thích các bước giải:
ta thấy
(1+2)^2=1^3+2^3
=> (1+2+3+4)^2=1^3+2^3+3^3+4^3
Ta thấy :
`(1+2)^2=1^3+2^3`
`(1+2+3)^2=1^3+2^3+3^3`
`⇒(1+2+3+4)^2=1^3+2^3+3^3+4^3`
Từ đó, ta rút ra công thức :
`[a+(a+1)+(a+2)+…+(a+n)]^2=a^3+(a+1)^3+(a+2)^3+…+(a+n)^3`